Development of free 25-hydroxyvitamin D3 assay method using liquid chromatography-tandem mass spectrometry. Issue 10 (7th October 2022) - Ishimine, Nau; Wu, Shixing; Ota, Ryusei; Takahashi, Koji; Takiwaki, Masaki; Sugano, Mitsutoshi; Tozuka, Minoru; Uehara, Takeshi
Abstract: The free hormone hypothesis has triggered controversies regarding the measurement of free vitamin D metabolites, such as free 25-hydroxyvitamin D (25(OH)D), as a suitable indicator for total vitamin D for clinical use. This issue can be addressed by developing a precise and accurate method for free 25(OH)D measurement. In the present study, a novel assay method for free 25(OH)D3 based on liquid chromatography-tandem mass spectrometry (LC-MS/MS) was developed. Sample preparation first involved ultrafiltration to remove vitamin D-binding protein-bound and albumin-bound 25(OH)D, followed by extraction with a column, derivatization, evaporation, dissolution, and injection into the LC-MS/MS system. The coefficient of variation of repeatability and reproducibility obtained were 3.8–4.5% and 4.8–5.9%, respectively. Satisfactory linearity ( r =0.999) was obtained up to 80 pg/ml. The lower quantification limit was 0.97 pg/ml and the S/N ratio on the peak of 1.0 pg/ml sample was 24.8 (which is more than the acceptable value of 10). The recovery rate was between 84.5 and 92.4% with a negligible matrix effect (94.5–104.9%). Levels of free 25(OH)D3, but not total 25(OH)D3, in the serum of the patients with chronic kidney disease (CKD) and hepatic cirrhosis (HC) were substantially lower than those in healthy subjects. The correlation coefficient between total and free 25(OH)D3 was 0.738 in all samples, while the linear regression equations were different between the patients with CKD and HC. In conclusion, LC-MS/MS assay for free 25(OH)D3 might be useful to evaluate high-throughput methods, including ELISA.